2019
DOI: 10.1002/cam4.1987
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between immune signature and high‐density lipoprotein cholesterol level in stage II/III colorectal cancer

Abstract: An increasing amount of evidence suggests that high‐density lipoprotein cholesterol (HDL‐C) is related to a positive prognosis in various cancers. However, the correlation between HDL‐C and the immune signature and the prognostic role of HDL‐C in stage II/III colorectal cancer (CRC) has not been previously reported. A total of 667 CRC patients were enrolled and divided into two groups based on the lower limit of normal HDL‐C values (0.78 mmol/L). We used Kaplan‐Meier curves and the Cox regression model to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…The NSCLC patients in this study received surgical resection, and so the immune system may play an important part in the elimination of potential residual micro-metastases. The anti-tumor effect of HDL-C both in humans and in vivo are associated with altered immune responses [ 42 , 43 ]. Speculatively, chemotherapy-related HDL-C and survival may be explained by the interaction between the cancer type, chemotherapy regimen and the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The NSCLC patients in this study received surgical resection, and so the immune system may play an important part in the elimination of potential residual micro-metastases. The anti-tumor effect of HDL-C both in humans and in vivo are associated with altered immune responses [ 42 , 43 ]. Speculatively, chemotherapy-related HDL-C and survival may be explained by the interaction between the cancer type, chemotherapy regimen and the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Low pre-operative HDL-C levels in patients with stage II/III CRC are associated with worse disease-free survival (DFS) and overall survival (OS) [ 29 ]. On the other hand, chemotherapy-related elevations in HDL-C levels in patients with non-metastatic CRC correlate with a longer DSF and OS [ 25 ].…”
Section: Hdl-c Levels and Hdl Subclass Distribution In Crcmentioning
confidence: 99%
“…A bulk of evidence indicates that the antitumor activity of apoAI in various malignancies is partially related to its effects on immunity [ 66 ]. Indeed, it was recently shown that serum HDL-C levels correlate with the specific immune signature of cancerous tissue in CRC patients, in particular with CD3 and CD8 markers, implying that high HDL-C and apoAI levels might be associated with enhanced recruitment and activity of CD3+ and CD8+ T cells, which exhibit antitumor activities [ 29 ]. In addition, in vitro studies have demonstrated that apoAI mimetics inhibit the proliferation, migration, and invasiveness of human colon adenocarcinoma cell lines [ 67 ], as well as diminish the viability and proliferation of murine colon adenocarcinoma cells [ 67 ].…”
Section: Functional Characteristics Of Hdl Particles In Crcmentioning
confidence: 99%
“…Cholesterol associate with LDL and HDL, or cholesterol derivatives are likely to have distinct and/or opposing effects [51][52][53][54][55]77]. Overall inhibition of fatty acid and/or cholesterol synthesis may thus induced complex outcomes.…”
Section: The Potential Interpretations For the Discrepancy In The Role Of Lipid Metabolism Reprograming In Cancermentioning
confidence: 99%
“…One speculation is that altered lipid profiles elicit immune response and such induced immune suppression. Reprogramming of cellular cholesterol metabolism has been shown to modulate the immune system [77,97,98]. Lipotoxicity induced cell death may be another reason.…”
Section: The Potential Interpretations For the Discrepancy In The Role Of Lipid Metabolism Reprograming In Cancermentioning
confidence: 99%